2010
DOI: 10.1002/nem.754
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and analysis for supporting multicast traffic by using multilayer multistage interconnection networks

Abstract: SUMMARYMultilayer multistage interconnection networks (MLMINs) integrate communication with network components and the components of parallel systems, especially when they service multicast traffic. This paper presents an approximate performance methodology for self-routing MLMINs that consist of two segments, each of which is composed of symmetrical switch elements. The first segment is subject to blocking situations with one mode of packet transmission policy (unicast). The second segment-the multilayer-is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Considering various analytical studies on multistage fabrics carefully, it can be pointed out that many researchers have observed that more switching power is needed in the final stages of a MIN compared with the first stages. 2,3,15,19,20 To overcome this behaviour, Tutsch and Hommel 18 introduced the so-called "multilayer MINs" (MLMINs). In a thorough quantitative study, Garofalakis and Stergiou 19 revealed that MLMINs present better performance behaviour compared with classic MINs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering various analytical studies on multistage fabrics carefully, it can be pointed out that many researchers have observed that more switching power is needed in the final stages of a MIN compared with the first stages. 2,3,15,19,20 To overcome this behaviour, Tutsch and Hommel 18 introduced the so-called "multilayer MINs" (MLMINs). In a thorough quantitative study, Garofalakis and Stergiou 19 revealed that MLMINs present better performance behaviour compared with classic MINs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An idea to solve this problem is the use of the concept of multi-layering. For instance, there have been already some multilayer fabric switches on the market that accommodate services for multicast traffic [18,44]. For instance, Cisco has built the MDS 9124 and MDS 9134, which are in fact typical multistage selfrouted switching devices.…”
Section: Reliability Analysis On Banyan-type Mins Typically Banyan Nmentioning
confidence: 99%
“…The Cisco MDS 9134 multilayer fabric switches can be used as the foundation for small, standalone storage area networks (SANs), or as an edge switch in large core-edge SAN infrastructures. The Cisco MDS 9134 can be stacked in pairs to form a 48-port or a 64-port 4 Gbps switch [18,44].…”
Section: Reliability Analysis On Banyan-type Mins Typically Banyan Nmentioning
confidence: 99%
See 2 more Smart Citations